A User-oriented UI/UX Application Design Using The Integration of Quality Function Deployment (QFD) and Design Thinking Methods - Koswara, Robby; Alifin, Fakhri Ikhwanul (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
UI / UX is essential in designing an application or website due to its impact on the user. With a decent and user-oriented UI/UX, users will experience high conformance and interact easily with the application or website, hence increasing the intensity of product usage and providing a better experience for users. However, the users' requirements are often neglected, making it difficult for the applications or websites to obtain a constant user number. Furthermore, this research aims to create a novel method to design UI/UX for CRM, which aligns with the needs and specifications of users. The data are collected using primary data through direct observation and questionnaires at an IT company called Numazu and its users. These data aim to measure and determine user needs and expectations by the integration of the Design Thinking and Quality Function Deployment (QFD) method. This research contributes to creating innovative and user-relevant UI/UX design methods, especially for CRM systems. The findings of this research also show an improvement in user experience through a user-oriented UI/UX design.